2013
DOI: 10.5005/jp-journals-10024-1332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Activity of Glass-ionomer Cement and Amalgam in Class Two Restorations by Streptococcus mutans Count Analysis at Fixed Intervals: An in vivo Study

Abstract: Glass ionomer cement should be preferred over amalgam in conservatively prepared restorations as it reduces the microbial activities due to fluoride release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Concerning the bacterial count by Dentocult strips for both groups, there was significant decrease in Streptococcus Mutans count from baseline in relation to different time periods. This result is in accordance with previous studies [24,25] who reported that, there was a significant reduction of SM levels in saliva immediately after 1 week following the ART approach using Fuji IX glass ionomer. Concerning the bacterial count of conventional glass ionomer group (group I) there was a significant difference between the baseline and the end of six month period.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the bacterial count by Dentocult strips for both groups, there was significant decrease in Streptococcus Mutans count from baseline in relation to different time periods. This result is in accordance with previous studies [24,25] who reported that, there was a significant reduction of SM levels in saliva immediately after 1 week following the ART approach using Fuji IX glass ionomer. Concerning the bacterial count of conventional glass ionomer group (group I) there was a significant difference between the baseline and the end of six month period.…”
Section: Discussionsupporting
confidence: 93%
“…Glass-ionomer cements (GICs) are well known for their cariostatic behavior, which is based not only on their antibacterial effect (Duque et al 2005;Tegginmani et al 2013) but also on the inhibition of bacterial acid production (Nakajo et al 2009) due to the fluoride release. Both of these properties will contribute to a lower acidity of the plaque around GIC compared with resin composites (Mayanagi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that glass ionomer cements (GICs) 1,2 have potential bioactivity, adhesion to hard tissues and also reduce the formation of plaque by Streptococcus mutans strains. [3][4][5][6][7][8][9][10][11][12] The antibacterial activity of glass ionomer cements (GIC) is mostly attributed to their fluoride and other ions release for secondary caries inhibiting effect, which has been already confirmed in vitro with lower demineralization depths of the glass ionomer groups adjacent to the dental hard tissue. [13][14][15][16][17][18][19] Thus, these cements are expected to actively control microbial biofilm formation, while biofilms modulate the release of fluoride from GICs.…”
Section: Introductionmentioning
confidence: 99%